Exploring the influence of cell configurations on Cu catalyst reconstruction during CO2 electroreduction - Woong Choi; Younghyun Chae; Ershuai Liu; Dongjin Kim; Walter S. Drisdell; Hyung-suk Oh; Jai Hyun Koh; Dong Ki Lee; Ung Lee; Da Hye Won (Nature Publishing Group, 2024)
Membrane electrode assembly (MEA) cells incorporating Cu catalysts are effective for generating C2+ chemicals via the CO2 reduction reaction (CO2RR). However, the impact of MEA configuration on the inevitable reconstruction of Cu catalysts during CO2RR remains underexplored, despite its considerable potential to affect CO2RR efficacy. Herein, we demonstrate that MEA cells prompt a unique reconstruction of Cu, in contrast to H-type cells, which subsequently influences CO2RR outcomes. Utilizing three Cu-based catalysts, specifically engineered with different nanostructures, we identify contrasting selectivity trends in the production of C2+ chemicals between H-type and MEA cells. Operando X-ray absorption spectroscopy, alongside ex-situ analyses in both cell types, indicates that MEA cells facilitate the reduction of Cu2O, resulting in altered Cu surfaces compared to those in H-type cells. Time-resolved CO2RR studies, supported by Operando analysis, further highlight that significant Cu reconstruction within MEA cells is a primary factor leading to the deactivation of CO2RR into C2+ chemicals.